Autologous cell membrane coatings on tissue engineering xenografts for suppression and alleviation of acute host immune responses. (November 2020) - Tao, Chao; Nie, Xiaolei; Zhu, Wenzhen; Iqbal, Jabed; Xu, Chenjie; Wang, Dong-An
Abstract: Xenogeneic extracellular matrix (ECM) based tissue engineering graft is one of the most promising products for transplantation therapies, which could alleviate the pain of patients and reduce surgery cost. However, in order to put ECM based xenografts into clinical use, the induced inflammatory and immune responses have yet to be resolved. Cell membrane is embedded with membrane proteins for regulation of cell interactions including self-recognition and potent in reducing foreign body rejections. In this study, a novel and facile method for evasion from immune system was developed by coating autologous red blood cell membrane as a disguise on xenogeneic ECM based tissue engineering graft surface. Porcine source Living Hyaline Cartilage Graft (LhCG) and decellularized LhCG (dLhCG) established by our group for cartilage tissue engineering were chosen as model grafts. The cell membrane coating was quite stable on xenografts with no obvious decrease in amount for 4 weeks. The autologous cell membrane coated xenograft has been proved to be recognized as "self" by immune system on cell, protein and gene levels according to the 14-day lasting in vivo study on rats with less inflammatory cells infiltrated and low inflammation-related cytokines gene expression, showing alleviated acute immune and inflammatory responses.